Analisis Kemampuan Literasi Dan Numerasi Siswa Kelas V Di SDN 41 Malewang Melalui Pelaksanaan AKM Kelas (Kampus Mengajar) - Nur Hidayah; Muhammad Syukur (Harmoni: Jurnal Ilmu Komunikasi dan Sosial, 2023)
Malewang 41 Elementary is one of the schools located in Polongbangkeng Utara sub-district, Takalar district, South Sulawesi Selatan Province. In carrying out its activities, this school is under the auspices of the ministry of education and culture. Teaching Campus is part of learning and teaching activities in basic education units from the Merdeka Learning Merdeka Campus (MBKM) program which aims to provide opportunities for students to learn and develop themselves through activities outside the classroom. The Teaching Campus aims to equip students with a variety of expertise and skills by partnering with teachers and schools in developing learning models, as well as fostering creativity and innovation in learning so that it has an impact on strengthening literacy and numeracy learning in schools.Reading and counting is a skill that must be possessed by every person and taught from an early age. Each student has a different level of reading ability, AKM can be used to evaluate students in reading and counting skills. Therefore, the purpose of this study was to determine the ability to read and numeracy, the factors that influence literacy and numeracy skills, and the way in solving literacy and numeracy problems of the fifth-grade students. This research uses a qualitative descriptive method with a case study approach. The location of the research is at SDN 41 Malewang. The research subject was fifth-grade students and the teacher who was responsible for AKM at SDN 41 Malewang. The research subjects were fifth-grade students and 5th batch of campus teaching students who was responsible for AKM at SDN 41 Malewang. The results showed that most of the fifth-grade students at SDN 41 Malewang who followed AKM include in the basic category. Their reading literacy and numeracy abilities are influenced by internal factors from within students and external factors from the family and school. The way that students solve AKM literacy questions is by doing easy questions first.